Cardiac rehabilitation for patients with heart failure: a national Danish register-based study of predictors of referral and outcomes. (29th July 2021) - Thygesen, LC; Zinckernagel, L; Dalal, H; Egstrup, K; Glumer, C; Gronbaek, M; Holmberg, T; Kober, L; La Cour, K; Nakano, A; Nielsen, CV; Sibilitz, KL; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation Background: Heart failure (HF) places a large burden on patients and society as a major cause of morbidity, mortality and healthcare costs. Participation in exercise-based cardiac rehabilitation (CR) in people with HF is a clinically and cost-effective strategy and recommended in international clinical guidelines. Purpose: The aims of this study were to: (1) examine the temporal trends and predictors of national CR referral, and (2) compare the risk of hospital readmission and mortality in those referred for CR compared to no referral. Methods: All patients in Denmark with incident HF were identified by the Danish Heart Failure Register in the period 2010 to 2018 (n = 33, 257) and CR referral assessed within 120 days of hospital admission. Multivariable logistic regression models were used to evaluate the association between CR referral and predictors and to compare risk of hospital readmission and mortality until 1 year between referred and not referred patients. Results: Overall, 45.0% of HF patients were referred to exercise-based CR, increasing from 31.7% in 2010 to 52.2% in 2018. Factors independently associated with higher CR referral were: NYHA functional class II, LVEF <50%, diagnosis of myocardial infarction and use of ACE inhibitor. Male gender, older age, region, unemployment, retirement, living alone, non-Danish ethnic origin, lower educational level, NYHA class IV, treatment for hypertension, existing chronic obstructive lung disease and stroke were associated with lower CR referral. CR referral was associated with lower risk of readmission (adjusted odds ratio: 0.90;95%CI: 0.85-0.95), HF-specific mortality (0.61; 0.39-0.95) and all-cause mortality (0.61; 0.55-0.69) as compared to no referral. Conclusions: Although CR referral has increased over time, only some 1 in 2 diagnosed HF patients in Denmark are referred to exercise-based CR. CR referral is associated with lower risk in readmissions and mortality. Strategies to promote CR referral including healthcare professional education on the benefits of CR and alternative methods of CR delivery are urgently needed to improve access to CR, especially for high-risk groups.